Eruption Cycle of Volcanic Rocks Based on Virtual Reality Technology - Yang, Jiqiang; Wang, Xing (Earth Sciences Research Journal, 2020)
The eruption cycle of volcanic rocks based on virtual reality technology is studied to reveal the spatial distribution of volcanic rocks and the genetic relationship between different lithologic assemblages, and effectively guide volcanic exploration. Taking Xujiaweizi fault depression and Yingshan depression in Songliao Basin as the research area, the monocular vision method of virtual reality technology is used to collect data from the study area. Then, the three-dimensional dynamic scene of the study area was constructed. Based on this, combined with the research steps and division basis of the volcanic eruption cycle, the eruption cycle of the volcanic region in the study area is studied. According to the characteristics of volcanic activity, volcanic facies sequence, and rock rhythm combination in Xujiaweizi fault depression, the first and three sections of Yingcheng formation are divided into three eruption periods according to the contact relationship between sedimentary strata and volcanic rocks in the eruptive intermittent period. Y1C1, Y1C2, Y1C3, Y3C1, Y3C2, and Y3C3 are respectively from bottom to top. Yingshan volcanic rocks in Yingshan depression are divided into three cycles and six periods. Each stage has significant stages and differences, and the eruption intensity is different. The overall performance is gradually enhanced, and the internal cycle is characterized by the first strong and then weak.